Endometrial cancer treatment and outcomes in Argentina: ECHOS-A real-world study - Claudia Soares; Gabriela Abreu; Juliana Queiroz; Thiago Luiz Nogueira da Silva; Patrícia Menezes; Mariano Carrizo; Paula Scibona; Nadia Elisabeth Savoy; Ventura A. Simonovich; María Cecilia Riggi; Diego Odetto; Florencia Cravero; et al. (Elsevier, 2024)
Objective: Real-world data for patients with endometrial cancer (EC) are limited, particularly in Latin America. We present treatment pattern findings from ECHOS-A - Endometrial Cancer Health Outcomes Study in Argentina. Materials and methods: A retrospective study using clinical data from privately insured patients with EC diagnosed from 2010 to 2019. Index (diagnosis proxy) was first date of an EC-related health term or treatment. Demographics, clinical characteristics, and FIGO staging were described. Disease progression and survival were assessed until study end, loss to follow-up, or death. Results: Of 805 patients with EC, 77.4 % (n = 623/805) received any treatment and 22.6 % (n = 182/805) received none. Among those treated, 31.8 % (n = 198/623) had first-line (1L) systemic therapy, and 45.5 % (n = 90/198) proceeded to second-line (2L) therapy. Mean follow-up was 33.6 (SD 31.8) months. Of those receiving any treatment, 87.3 % (n = 544/623) had FIGO stage data (I, 62.9 %; II, 18.6 %; III, 13.6 %; IV, 5.0 %). Treatment by class in 1L and 2L, respectively, were platinum chemotherapy, 73.7 %, 36.7 %; non-platinum chemotherapy, 73.7 %, 62.2 %; immunotherapy, 1.0 %, 11.1 %; hormone therapy, 17.7 %, 26.7 %. Carboplatin/paclitaxel was the most frequent 1L (52.5 %) and 2L (14.4 %) regimen. Mean time to progression was 14.1 (SD 16.3) and 8.8 (SD 8.3) months in 1L and 2L, respectively. Adjusted 1- to 5-year risk of progression/death was 46.5-77.5 % and 65.0-86.2 % in 1L and 2L, respectively. Conclusions: Approximately one-quarter of patients with EC received no treatment, and approximately two-thirds were not treated with 1L systemic therapy. Efforts to better understand the reasons for these treatment patterns are crucial for improving patient outcomes.